Students Perception Towards The Use of Animated Movie in Vocabulary Lesson (A Case Study) - Rahmayanti, Kartika Tri; Ridwan, Iwan; Kamil, Acep Bahrum (Peneliti.net, 2025)
This study aims to explore students' perceptions towards the use of animated movies in vocabulary lessons at SKB (Sanggar Kegiatan Belajar) Purwokerto. Using a descriptive qualitative approach, this research involved 20 seventh-grade students at SKB Purwokerto. Data were collected through a questionnaire consisting of 20 questions, as well as in-depth interviews with 7 students to enrich the findings. The results of the study showed that the majority of students had a positive perception of the use of animated movies in vocabulary lessons. They felt that animated movies made the learning process more engaging and helped them understand and remember new vocabulary more easily. Additionally, animated movies were also considered to increase students' motivation to learn. However, some students expressed negative perceptions, such as the use of animated movies taking up learning time and causing confusion due to the fast pace. Based on these findings, it is suggested that teachers consider using animated movies as an innovative and effective medium for vocabulary lessons, while still providing clear and structured guidance. This study contributes to the development of creative teaching strategies in English education at SKB Purwokerto.